Inception of eco-psychology elements in environmental education among teacher trainees - Tiwi Kamidin,; Azizi Muda,; Samsilah Roslan,; Mohd Majid Konting,; Jamaluddin Md Jahi,; Noriati A. Rashid, (Environmental Management Society, Malaysia, 2010)
Even though Environmental Education has been implemented since 1990s in national curriculum, still some researchers finding indicated that more people believed and care of their environment but not reflected to their daily behaviour. Some researchers also stated that this is because of our psychological and spiritual (psyche) is split from the natural world. So, we need to heal our mental health especially our psychological and re-embed psyche (spiritual) in the natural world. This study assessed the impact of inception ecopsychology elements in Environmental Education among trainee teachers on attitudes toward environment (ATE), ecopsychological and spiritual values. A mixed methods design was used to evaluate the effect of inception ecopsychology elements in Environmental Education on ATE, ecopsychological and spiritual values. Initial findings showed that there are significant differences on ATE, ecopsychological and spiritual values between experimental and control groups. Experimental groups who was taught with ecopsychology elements in Environmental Education teaching and learning activities showed slightly higher on ATE, ecopsychological and spiritual values mean scores. Qualitative findings also showed that the respondents from experimental groups believed they considered changing their attitudes, ecopsychological and spiritual values toward environment after participated in the class. Findings from this study suggested the implementation of EE should incept ecopsychology elements in order to strengthen internal motivation and sensitivity toward environments. Therefore, suggested activities should be incepted in Environmental Education without denying existing activities and syllabus